Relações entre os Pensamentos Algébrico e Computacional em atividades propostas por coleções de Livros Didáticos - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This investigation aims to analyze how collections of Mathematics textbooks (Final Years of Elementary and High School), approved by the PNLD, expose situations that require the analysis/construction of algorithms in the study of the sequences concept. For this, we opted for a qualitative research, using assumptions of Content Analysis. The data production sources are eight collections of Mathematics textbooks from the Final Years of Elementary School, approved by PNLD 2020, and nine collections from High School, approved by PNLD 2021. Data analysis was based on the following criteria: types of patterns (repetitive, numeric, figural); types of sequences (recursive, non-recursive and associated function types); phases of a pattern; PC concepts/pillars (abstraction, algorithm, decomposition and pattern identification); representations used for analysis and/or construction of algorithms (natural language, flowchart, programming language); in selected textbook collections. When analyzing the 17 textbook collections, 47 situations were identified (26 in Elementary School and 21 in High School) based on the mentioned criteria. Regarding the types of patterns, it was found that most situations in both Elementary and High School explore the numerical pattern. Regarding the recursion or not of the sequences, in Elementary School, 11 situations explore recursive sequences and in High School, 11 situations explore non-recursive sequences, associated with linear function. Regarding the 3 phases of a pattern, in Elementary School, 12 situations explore the 3 phases and in High School, only three situations explore the 3 phases. Regarding Elementary School collections, it was found that the 26 situations make it possible to explore the abstraction and analysis/construction of the algorithm; 17 make it possible to explore, in addition to abstraction and analysis/construction of the algorithm, the identification of patterns and only three make it possible to explore, in addition to abstraction, analysis/construction of the algorithm and identification of patterns, the decomposition, thus, only three situations allow explore the four concepts/pillars of PC. It should be noted that 24 situations explore the analysis/construction of the algorithm in a flowchart/scheme, however, only 9 request its construction. In the high school collections, it was found that 19 situations make it possible to explore the abstraction and analysis/construction of the algorithm, nine situations make it possible to explore, in addition to abstraction and analysis/construction of the algorithm, the identification of patterns and no situation allows exploring the decomposition, thus, no situation makes it possible to explore the four concepts/pillars of the PC. It is noteworthy that 14 situations explore the algorithm construction in flowchart/scheme, however, only 10 request its construction. It is understood that teachers will need to resort to other resources or textbooks to be able to develop the skills exposed in the BNCC, which involve algorithms/flowcharts.
Keywords: Álgebra; Computação; Resolução de Problemas; Padrão; Algoritmo; Computing; Problem Solving; Pattern; Algorithm; CIENCIAS EXATAS E DA TERRA